The effect of two cooperative learning models on the achievement of second grade students - Teachers College in the matter of differentiation (Journal of the College of Basic Education, 2023)
What distinguishes mathematics from other academic subjects are the difficulties that students face in understanding it, which generates negative attitudes towards it in particular and towards subjects that use mathematics to solve its problems. It uses simple mathematics like the commercial or industrial branch.The problem appears more among the students whom we are preparing to be teachers in the future. The impact of this problem will not be confined to the students themselves, but will go beyond that to the students who will teach them in the future. The student who is not able to study the subject will inevitably reflect on his students who will study them in the future. Many studies have indicated this problem, such as the study of (Bottage 1973), the study of (Abu Omaira 2000) and the study of (Al-Saadi 2001), and perhaps among the subjects that students suffer from The problem of understanding it is differentiation, and the reason for that is that this subject is difficult because of the following:1- The large number of theories that require proof, and it is known that the proof takes place within the higher levels of Bloom's cognitive levels, such as analysis and synthesis, and every step in the proof needs explanation, which falls within the levels of logical thinking. Likewise, the proof constitutes a difficulty and a problem for students since they studied geometry in the intermediate stage and from Then prep.2- The majority of issues in differentiation require more than one operation to solve them. When a student solves a problem such as <2 ||| Need to bring:A- The concept of absolute value and the concept of inequality.B- The concept of union as well as intersection, because the student needs them to identify and define the solution areas on the number line.In addition to the foregoing, the student, since the elementary stage, fails to solve problems that contain more than one operation.Perhaps the reason that leads to the students' lack of understanding of this subject is that the majority of university teachers used the method of lectures, and the lecturers take all the lectures upon themselves, and allow students to participate, as they are limited.Hence, there has become an urgent need to experiment with new methods in teaching this subject that lead to making its absorption accessible to students, and thus positive attitudes are generated towards it, and this will certainly be reflected on students’ achievement in it. From here, the problem of the current research is determined in answering the following question:Is the achievement of the second grade students - Teachers College - Mathematics branch affected by using two models in cooperative learning compared to the achievement of their peers studying the same subject using the lecture method?